The effect of stress on egg quality in farmed Atlantic Cod (Gadus morhua L.) - Natário, Silvestre Ramos (2011)
The Atlantic cod (Gadus morhua), is a prestigious species of fish that belongs to the Gadidae family, and is considered a promising species for future aquaculture in the northern hemisphere. Cod production has grown exponentially since the beginning of the millennium. The but development of cod farming has been hampered by bottlenecks in the production such as deformities, diseases as francisellosis, slow growth and early maturation, and in addition relatively low market prices compared to present production costs. Farming of cod relies on a stable supply of high quality eggs. Egg quality and production is dependent not only upon the female condition and hence broodstock diet, but can be negatively affected by stress. In addition, farmed females often fail to release their eggs, become eggbound and die. The project “Why do Atlantic cod females become eggbound? Studies on possible causes and mechanisms” (Research Council of Norway, grant no 190187/E40) investigates the physiological events during normal and abnormal (eggbound) spawning, with the aim to determine factors that may cause the problems. Two factors that may affect these are investigated in this project; The first is dietary lipid content as this correlates to gonadosomatic index (GSI, gonad weight as % of total weight). The fecundity of farmed cod is about 50% higher than wild cod, and one could suspect that abnormally large gonads would increase the problems with eggbound females. The second variable is stress, either directly due to distorted spawning behaviour or indirectly through the eicosanoid cascade. Eggs of poor quality can have a negative impact on production resulting in slow growth, high mortality rate and deformities. In this master it has been focused on the egg production from farmed cod fed either a high (20%) or a low (13%) fat diet, and either physically stressed or not. The stress treatment, imposed randomly once a week, consisted of reducing the water level to a height of 15 cm from the bottom, and for 1 minute the fish were chased with a landing’s nets. The low-stress treatment was nothing more than keeping fish in tanks. The amount of eggs spawned in the tanks was measured through the spawning season and used to calculate fecundity, and egg quality assessed by egg diameter, fertilization, deformities, and hatching rate. The dietary treatment affected final weight; cod fed the low fat diet, had a lower final weight after spawning compared with fish that were fed a high fat diet. The fecundity, expressed as total production of eggs spawned, was affected by diet. The fishes that were fed with the low fat diet had a lower fecundity than the fish fed with a high fat diet. The duration of the spawning season as like the fecundity was also influenced by the stress; the cod in the high stress treatment prolonged their spawning period compared to the low stress group. Egg diameter decreased during the spawning season in all treatments, The fertilisation rate was directly influenced by the type of treatment during the spawning season, but no significant differences were found when assessed 1 or 2 days after stress. Hatching rate was different between diets, but when combined with stress, only fish fed the low fat diet exhibited different rates of hatching. Finally, the rate of deformities did not differ between treatments. In a general assessment, good egg quality is obtained by finding a balance between diet and type of management. Furthermore, fish fed with high fat levels appear more tolerant to stressful activities. Consequently, egg quality, has to be defined by a combination of several parameters. It is also important not to set aside the inclusion of new parameters that may be decisive in order to minimize misclassification.